2021
DOI: 10.1038/s41594-021-00560-2
|View full text |Cite
|
Sign up to set email alerts
|

Target-induced clustering activates Trim-Away of pathogens and proteins

Abstract: Trim-Away is a recently developed technology that exploits off-the-shelf antibodies and the E3 RING ligase and cytosolic antibody receptor TRIM21 to carry out rapid protein depletion. How TRIM21 is catalytically activated upon target engagement, either during its normal immune function or when re-purposed for targeted protein degradation, is unknown. Here we show that a mechanism of target-induced clustering triggers intermolecular dimerisation of the RING domain, to switch on the ubiquitination activity of TR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 63 publications
1
91
0
Order By: Relevance
“…Studies have shown dimerisation of the catalytic RING domains to be necessary for ubiquitinating activity in most TRIM proteins studied so far (48). This holds true for TRIM21, with a recent study demonstrating that dimerisation at TRIM21's coiled-coil directly enabled catalytic activity (49). Mutation of residues at the antiparallel coiled-coil dimer interface was sufficient to inhibit auto-ubiquitination of the RING domain, following infection of HEK293T cells with antibody-coated adenovirus.…”
Section: Coiled-coilmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies have shown dimerisation of the catalytic RING domains to be necessary for ubiquitinating activity in most TRIM proteins studied so far (48). This holds true for TRIM21, with a recent study demonstrating that dimerisation at TRIM21's coiled-coil directly enabled catalytic activity (49). Mutation of residues at the antiparallel coiled-coil dimer interface was sufficient to inhibit auto-ubiquitination of the RING domain, following infection of HEK293T cells with antibody-coated adenovirus.…”
Section: Coiled-coilmentioning
confidence: 93%
“…Furthermore, forced RING domain dimerisation ( via RING-linker-RING constructs) increased ubiquitin discharge activity. A proposed model of “clustering-induced activation” suggests dimerisation of RING domains makes E2-ubiquitin engagement with TRIM21 and subsequent polyubiquitin discharge more energetically favourable ( 49 ).…”
Section: Trim21 Structurementioning
confidence: 99%
“…An OptoTrim-Away construct, which contains TRIM21 fused with CRY2 and an anti-GFP nanobody vhhGFP4, has been generated to demonstrate light-inducible degradation of GFP-tagged protein ( FIGURE 10 C ). Given that the RING domain alone is sufficient to trigger clustering and proteasomal degradation, a minimal version of OptoTrim-Away was created to cause target degradation to a similar level of full-length TRIM21 ( 349 ). Red or far-red light-inducible degradation systems are yet to be developed to enable paralleled degradation of multiple endogenous targets in the same cells.…”
Section: Application Of Optogenetics In Physiological Processesmentioning
confidence: 99%
“…TRIM21 recognizes antibody-bound pathogens through a high-affinity interaction with the Fc domain of the antibody and tags the antibody-bound pathogens for ubiquitination and degradation. Clift et al repurposed TRIM21 to establish a method called Trim-Away that targets endogenous proteins for proteasomal degradation using endogenous or exogenous TRIM21 and antibodies that bind to the POI (Figure 2b) [30,31]. Notably, this technique enables the selective degradation of post-translationally modified protein and splice or mutant protein variants, by using a specific antibody, while preserving the unmodified/wild-type protein.…”
Section: Antibody-based Approachesmentioning
confidence: 99%